Self-efficacy and cues to action: Two main predictors of modified version of diet quality index in Iranian adolescents - Keshani, Parisa; Salehi, Moosa; Kaveh, Mohammad Hossein; Faghih, Shiva (Progress in Nutrition, 2018)
Background: The purpose of this study was to examine the association between health belief model (HBM) constructs and a modified version of diet quality index in Iranian adolescents. Methods: One thousand and fifty five adolescents aged 13-15 years old completed this cross-sectional study. Participants were selected from secondary schools in Shiraz, one of the megacities of Iran, using stratified random sampling. A modified version of revised children’s diet quality index (M-RCDQI), was calculated for each adolescents and its association with the model construct was assessed using linear regression. Results: Mean M-RCDQI score was 58.91±8.58 out of the total of 90 points. Among the M-RCDQI components, the worse scores were obtained by dairy intake, dietary fiber and vegetables in which less than 20% of the students reached maximum score. Among HBM constructs, cues to action (B=0.194, p=0.003) and self-efficacy (B=0.04, p=0.007) had positive, significant association with adolescents’ diet quality. Also there was a positive, significant association between cues to action and fruits consumption (B=0.026, P=0.026), and a negative significant association was seen between cues to action and total fat intake (B=-0.629, p=0.021). Furthermore, self-efficacy had a direct significant association with dairy intake. Conclusion: M-RCDQI could be a suitable tool for assessment of diet quality index and it is recommended for use in further studies in similar populations. Cues to action and self-efficacy would both be effective mediators in improvement of nutritional behavior among adolescents.